1988
DOI: 10.1128/aac.32.10.1477
|View full text |Cite
|
Sign up to set email alerts
|

Influence of storage and susceptibility test conditions on stability and activity of LY163892 and four other cephalosporins

Abstract: A new carbacephem analog of cefaclor, LY163892, was examined along with four other cephalosporins for chemical stability and for antibacterial activity under a variety of susceptibility test conditions. LY163892 was found to be markedly more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
1

Year Published

1990
1990
1999
1999

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 7 publications
0
5
1
Order By: Relevance
“…The infrequency of cefaclor resistance in this study and the previous study (9) is in contrast to the high rate of resistance (e.g., 60%) reported in two prior multicenter studies (18,19). This is perhaps due to the fact that cefaclor MICs are often twofold higher when tested in lysed horse blood supplemented Mueller-Hinton broth (as used by Jones and colleagues [18,19]) than in Haemophilus test medium (21), and perhaps is also due in part to the documented instability of cefaclor in culture medium (20). These differences may also be a reflection of the relative lability of cefaclor to the TEM-1 ,-lactamase of H. influenzae (19) which may result in elevated MICs at increased inoculum concentrations.…”
Section: Discussioncontrasting
confidence: 50%
“…The infrequency of cefaclor resistance in this study and the previous study (9) is in contrast to the high rate of resistance (e.g., 60%) reported in two prior multicenter studies (18,19). This is perhaps due to the fact that cefaclor MICs are often twofold higher when tested in lysed horse blood supplemented Mueller-Hinton broth (as used by Jones and colleagues [18,19]) than in Haemophilus test medium (21), and perhaps is also due in part to the documented instability of cefaclor in culture medium (20). These differences may also be a reflection of the relative lability of cefaclor to the TEM-1 ,-lactamase of H. influenzae (19) which may result in elevated MICs at increased inoculum concentrations.…”
Section: Discussioncontrasting
confidence: 50%
“…This antibiotic is less susceptible than ampicillin to the action of the commonly found TEM-1 P-lactamase in H. influenzae (8,11,15,27) and demonstrates good antibacterial activity against such P-lactamase-producing strains (12,13,17,19,35). A study (16) reported a reduced activity of cefaclor against 3-lactamaseproducing H. influenzae, a discrepancy that could be due to specific test media, inoculum size, and the known instability of cefaclor in test medium (17,18).…”
mentioning
confidence: 99%
“…This antibiotic is less susceptible than ampicillin to the action of the commonly found TEM-1 P-lactamase in H. influenzae (8,11,15,27) and demonstrates good antibacterial activity against such P-lactamase-producing strains (12,13,17,19,35). A study (16) reported a reduced activity of cefaclor against 3-lactamaseproducing H. influenzae, a discrepancy that could be due to specific test media, inoculum size, and the known instability of cefaclor in test medium (17,18).Cefaclor has been used clinically for about 12 years, and despite its extensive use worldwide, H. influenzae isolates remain highly susceptible to the drug (12, 35). This is in contrast to the high prevalence of ampicillin resistance which is now observed in 15 to 50% of H. influenzae clinical strains (6, 7,26).…”
mentioning
confidence: 99%
“…The authors suggest that the efficacy of an antibiotic can be assessed "only by performing randomized comparative studies in patients with [acute otitis media] from whom initial MEF culture is obtained immediately before antibiotic administration and a second one during the course of treatment." This position may be inappropriate for several reasons: (1) Current clinical trial guidelines explicitly require a determination of clinical and microbiologic end points after the end of therapy [2][3][4]; (2) although several studies have been cited to support the appropriateness of during-therapy bacteriologic end points, those reports do not clearly define the predictive value of this end point for standard posttherapy clinical or bacteriologic end points [5,6]; (3) the method of determining bacterial growth in MEF fails to account for known differences in chemical stability between cefaclor and cefuroxime ex vivo [7,8].…”
Section: Cefaclor and Cefuroxime Axetil In The Treatment Of Otitis Mementioning
confidence: 99%